A prioridade do correto sobre o bem como forma de garantir a estabilidade em sociedades marcadas pelo pluralismo razoável - Barreira, Carolina Matedi (2018)
The research examines a priority of the right over the good in John Rawls's book "Political Liberalism", by means of basic concepts of Justice as Fairness, highlighting reasonable political pluralism, political conception of justice and political construtivism. The intent is to demonstrate how that priority is the crucial element of Political Liberalism, and the vital role in justice as fairness. It also tries to demonstrate that ideas of right and the good are complementaries, and that priority of the first is more adequate to guarantee stability of societies marked by the fact of reasonable pluralism. The aim is to expose how this can benefit democratic societies marked by a profound plurality of ideias of good,which justifies the relevance of research on Rawls today.